Efficacy of Cognitive Therapy for Body Dysmorphic Disorder: A Randomized Controlled Pilot Trial. Issue 1 (January 2023) - Ritter, Viktoria; Schüller, Johanna; Berkmann, Eric M.; von Soosten-Höllings-Lilge, Laura; Stangier, Ulrich
Highlights: Evaluated efficacy of cognitive therapy for body dysmorphic disorder (CT-BDD) in 40 BDD patients. CT-BDD was significantly superior to wait-list in BDD and related symptoms (e.g., insight) at Week 12. Shame and insight mediated changes in BDD during treatment at Week 12. At posttreatment, BDD and related symptoms (e.g., insight) further significantly improved. Treatment gains were maintained at 3- and 6-month follow-up. Abstract: Dysfunctional cognitive processes and maladaptive interpersonal patterns have been postulated to maintain body dysmorphic disorder (BDD). The present trial evaluated CT for BDD (CT-BDD), which includes modules targeting maladaptive cognitive processing in BDD, as well as elements of schema therapy related to interpersonal problems. We investigated whether (a) CT-BDD is effective, as compared with a wait-list (WL) group at Week 12; (b) outcome of CT-BDD is maintained at posttreatment and 3- and 6-months follow-up; and (c) whether changes in shame and insight mediate changes in BDD symptom severity. Forty adults with BDD were randomized to 36 weeks immediate CT-BDD ( n = 21), or to 12-week WL ( n = 19). At Week 12, immediate CT-BDD was significantly superior to WL in clinician-rated BDD symptom severity, insight, self-reported BDD symptoms, shame, depression, general symptomatology, and life satisfaction. Changes in outcomes were associated with moderate to large effect sizes at Week 12. Reductions in shame and increase in insight separately mediated changes in BDD symptom severity during treatment at Week 12. From baseline to posttreatment, significant improvements occurred within CT-BDD in clinician-rated symptom severity, insight, depression, global functioning, self-reported BDD symptoms, shame, depression, general symptomatology, and life satisfaction. At posttreatment, improvements were associated with large effect sizes and were maintained at 3- and 6-month follow-up. Preliminary results support the efficacy of CT-BDD. Addressing interpersonal problems in addition to cognitive dysfunctions may increase the benefit of CBT for BDD patients.